Development of a novel robotic system for joint mechanical tests using a real-time controller - Kei KIMURA; Hiromichi FUJIE (Nihon Kikai Gakkai ronbunshu, 2015)
Application of robotic systems to the field of joint biomechanics studies has been performing in the last 2 decades. While a variety of studies have employed commercially available articulated robots we have designed and developed a material testing machine-like 6-degree of freedom (DOF) robotic system for higher load capacity and accuracy. The previous system consists of serially linked 2 translational and 3 rotational axes and a translational axis. All the servomotors at the 6 axes are controlled by a PC through a high-speed motion network. In the present study, we developed a novel 6-DOF robotic system that has a decoupled mechanism consisting of serially linked 3 translational axes and serially linked 3 rotational axes. All the servomotors at the 6 axes are controlled by a real-time controller through the EtherNet and EtherCAT. With knee joints fixed to the robotic system, either force control or position control can be applied with respect to the 6-DOF knee joint coordinate system. The velocity-impedance control was modified and applied to the force control while the velocity control was applied to the position control. The clamp-to-clamp stiffness of the novel robotic system was 541-1027 N/m and 262-355 Nm/rad which are more than 1.5 times higher than those of previous system. Responses to a step-function force input and a ramp-function force input were faster and more precise in the novel system than in the previous system. Moreover, joint forces and moments during 2-DOF and 6-DOF joint loading tests were controlled more precisely in the novel system than in the previous system. These results indicate the superiority of the novel robotic system over previously developed robotic systems. We believe that, with the system, it is possible to simulate physiological situations of the knee joint such as slow gait, standing up from a chair, and so on.